Argentina's Abandonment of the Rule of Law and Its Aftermath - Andrés A. Gallo; Lee J. Alston (Washington University Journal of Law & Policy, 2008)
In this Essay we show how, in the last sixty years, political and economic instability in Argentina have been accompanied by judicial instability. As a consequence, Argentina lacks adherence to the rule of law with deleterious effects on domestic business and foreign investment. We contend that in order to reach sustainable growth, Argentina has to solve this institutional problem. Otherwise, economic growth can surge in the short run but it will be unsustainable in the long run.
Keywords: Rule of law – Argentina; Economic development – Argentina; Institutional economics; Political stability; Argentina